Butanol and ethanol producing from cassava wastewater - Chogi, Marianne Akemi Neroni; Araújo, Ana Carolina Vieira; Silva, Ariovaldo José da; Duarte, Iolanda Cristina Silveira (Revista Hipótese, 2022)
The objective of this study was to evaluate the influence of different inocula on the production of butanol and ethanol from cassava wastewater. The inoculums used were Clostridium beijerinckii and cattle manure. Only the culture of C. beijerinckii produced butanol in yield of 0.014 g.g-1 and yield rate equal to 0.002 g/L.h-1. Ethanol was produced by cattle manure in yield of 0.51 g.g-1 and yield rate equal to 0.002 g/L.h-1.
Keywords: Butanol; Ethanol; Cattle Manure; Cassava Wastewater